Design of a 27-level cascaded converter as FACTS device for voltage sag mitigation - Nikouei B.; Tan N.M.L.; Taghizadeh S.F.; Younis M.A.A. (Taylor and Francis Ltd., 2023)
Electric power transmission; Power control; Power converters; Static synchronous compensators; Voltage stabilizing circuits; Cascaded converters; Design and control; Flexible ac transmission system (FACTS); Mitigating devices; Sag mitigation; Static synchronous series compensator; Transmission voltage; Voltage sag mitigation; Flexible AC transmission systems